Nitric oxide deficiency decreases C-repeat binding factor-dependent and -independent induction of cold acclimation. (14th March 2019) - Costa-Broseta, Álvaro; Perea-Resa, Carlos; Castillo, Mari-Cruz; Ruíz, M Fernanda; Salinas, Julio; León, José
Abstract : NO regulates cold acclimation through C-repeat binding factor-dependent and -independent pathways by regulating anthocyanin biosynthesis and ABA sensitivity. Abstract: Plant tolerance to freezing temperatures is governed by endogenous components and environmental factors. Exposure to low non-freezing temperatures is a key factor in the induction of freezing tolerance in the process called cold acclimation. The role of nitric oxide (NO) in cold acclimation was explored in Arabidopsis using triple nia1nia2noa1-2 mutants that are impaired in the nitrate-dependent and nitrate-independent pathways of NO production, and are thus NO deficient. Here, we demonstrate that cold-induced NO accumulation is required to promote the full cold acclimation response through C-repeat Binding Factor ( CBF )-dependent gene expression, as well as the CBF-independent expression of other cold-responsive genes such as Oxidation-Related Zinc Finger 2 ( ZF/OZF2 ). NO deficiency also altered abscisic acid perception and signaling and the cold-induced production of anthocyanins, which are additional factors involved in cold acclimation.